An update on small bowel endoscopy. Issue 3 (May 2017) - Ching, Hey-Long; McAlindon, Mark E.; Sidhu, Reena
Abstract : Purpose of review: The breakthrough success of capsule endoscopy and device-assisted enteroscopy has inspired researchers to test and push the boundary of these technologies. The authors herein summarize the latest and most significant studies with clinical impact. Recent findings: Competing capsule endoscopy models have enriched the platform of this wireless device. The role of capsule endoscopy in Crohn's disease is expanding as we learn more of the significance of disease distribution and response to treatment. The benefit of capsule endoscopy in abdominal pain has previously been sceptical, but may have a role. Device-assisted enteroscopy demonstrates significant benefit in the management of patients with Crohn's disease and Peutz–Jeghers syndrome. On the contrary, long-term data suggest that endotherapy to small bowel angioectasia may not be as beneficial to patients as we once thought. The role of device-assisted enteroscopy in novel territory, including coeliac disease and endoscopic retrograde cholangiopancreatography, continues to be tested. Summary: The limit of capsule endoscopy and enteroscopy is yet to be reached. Accumulating long-term data alludes to the benefits of our current practice while spawning novel indications for small bowel endoscopy.